Energia elétrica com biogás no agronegócio do Oeste do Paraná sob a ótica da nova economia institucional - Marques, Felipe Souza (2021)
The animal protein production in an integrated system has two very strong characteristics, the demand for electricity and the production of manure, first an input for production, and the other, an environmental liability. Based on these characteristics, efforts were made to develop biogas projects for electricity with a positive impact on the environment. The west of Paraná presents itself as a national reference in technological arrangements of projects of this nature. The west of Paraná has innovative projects using different substrates to produce biogas and apply it for energy purposes, whether as biomethane, thermal use or electricity generation. Especially in the electricity sector, the region stands out for developing technologies and business models with some impact, such as distributed generation, for example, and more recently, microgrids of electricity. However, even with several positive externalities, there are still few projects and little involvement of cooperatives and integrators in this theme. This thesis seeks to understand the barriers to the growth of electricity generation with biogas in western Paraná through the perspective of the new institutional economy. Through this approach, it was possible to identify that the lack of knowledge and information asymmetry allow the opportunistic behavior of agents. It was also possible to highlight the importance of sectoral articulation to define a single agenda for biogas, especially aimed at differentiating it from other sources of electric energy. Cooperatives and agribusiness integrator companies have a great opportunity to lead the growth in the number of biogas plants for electric power generation in western Paraná from the moment they undertake a vertical integration system for projects of this nature.